Three-dimensional kinetic function of the lumbo-pelvic-hip complex during block start - Sado, N.; Yoshioka, S.; Fukashiro, S. (PLOS ONE, 2020)
Previous studies on joint kinetics during track and field block starts have been limited to lower-limb sagittal kinetics; however, we hypothesised that lumbopelvic extensors, lateral flexors, and hip abductors also act as substantial energy generators. The present study aimed to examine the three-dimensional lumbo-pelvic-hip kinetics to better understand the generation of mechanical energy during a block start. 3D kinematic and force data during block starts of 10 m maximal sprinting in 12 male sprinters (personal best in a 100 m sprint, 10.78 ± 0.19 s [range, 10.43-11.01 s]) were captured using a motion capture system and force platform. The three-dimensional lumbo-pelvic-hip kinetics were calculated. The peak lumbosacral extension torque (3.64 ± 0.39 Nm/kg) was significantly larger than any other lower-limb and lumbosacral torques (<3.0 Nm/kg). It was suggested that large lumbopelvic extension torques are needed during the block start to anchor the pelvis by cancelling out both hip extension torques acting on the pelvis, leading to hip extensor-induced thigh sagittal rotations rather than pelvic posterior tilt. During the double-stance phase, the lumbosacral extensors generated mechanical energy (0.35 ± 0.16 J/kg, 14 ± 4% of the sum of lumbosacral and lower-limb net joint work). During the single-stance phase, the sum of the net mechanical work by lumbosacral lateral flexors and front hip abductors was 0.35 ± 0.14 J/kg, which comprised 9 ± 3% of the sum of the net joint work. The results lead to the speculation of the importance of strengthening not only the leg extensors, but also the lumbopelvic extensors, lateral flexors, and hip abductors for block starts. Further training studies to verify this speculation will improve training strategies for the track and field block start performance.